Marine nature-based solutions: Where societal challenges and ecosystem requirements meet the potential of our oceans. (October 2022) - Riisager-Simonsen, Christian; Fabi, Gianna; van Hoof, Luc; Holmgren, Noél; Marino, Giovanna; Lisbjerg, Dennis
Abstract: Nature-Based Solutions (NbS), a concept introduced in the late 2000s, has developed rapidly during the last years and is now frequently appearing in a broad spectrum of policies developed within the European Union. Its role in marine policies and research programmes is however still limited, but is likely to increase as NbS are adopted as key terminology in both biodiversity strategies and the EU taxonomy for sustainable financing. This will enhance the need for scientific advisory institutions to provide evidence-based advice on potential impacts of various combinations of marine NbS. To facilitate a critical debate about the prospects and pitfalls related to the operationalisation of marine NbS in an EU context, this paper provides an analysis of core definitions, potential categories of marine NBS and a suite of case studies. Coastal waters, shelf and open oceans present multiple options for testing new and scaling up known NbS, which could support both environmental restoration simultaneously with addressing multiple societal challenges, paving the way for a new level of ecosystem-based management. However, as the acceptance of NbS types will depend on ecosystem state and thus history, it will be a significant task to consistently communicate why some solutions may count as a NbS in some areas, while not in others. To conclude, the paper therefore raises a set of research priorities and policy advice aimed at ensuring the successful advice and deployment of marine NBS in support of multiple societal goals. Highlights: Nature-based solutions is gaining momentum globally as a concept with increases in marine scientific advise anticipated Many opportunities for nature-based solutions in European waters to address societal challenges beyond climate change Successful operationalization challenged in EU by elusive definitions and lack of criteria leading to a risk of greenwashing Attention needed from European policy makers and research and innovation funding entities to address policy and knowledge gaps